PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA PEMBELAJARAN ALTERNATIF DALAM MATA KULIAH PEMROGRAMAN: Studi kasus Mata Kuliah Pemrograman Mobile di STMIK STIKOM Indonesia - Ardiana, Dewa Putu Yudhi; Wahyu Aristana, Made Dona (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
The development of information and communication technology has an impact on the availability of various alternatives for delivering learning materials. One of the alternative channels to convey information is social media, which shows growth every year. This research takes a case study in the mobile programming course at the STMIK STIKOM Indonesia campus. This study aims to develop learning media by utilizing Instagram social media as a means of delivery as an effort to increase learning motivation and the selection of learning media that can be used in learning. The selection of social media Instagram as a means of delivery is based on an online survey conducted on STMIK STIKOM Indonesia students in February 2021, which shows that 90% are actively using Instagram. The model used in this research is Decide Design Development - Evaluation (DDD-E) as a learning media development framework. This study uses testing from material experts, media experts and small group evaluations to determine the feasibility of learning media so that they can be used in learning.